1998
DOI: 10.1038/sj.sc.3100646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods to assess muscular strength in individuals with spinal cord injury

Abstract: The aim of the project was to compare three methods for measuring muscle strength in individuals with SCI: the manual muscle test (MMT), the hand-held myometry and the isokinetic dynamometry (Cybex). Thirty-eight (38) subjects, 31 men and seven women (age range=14 ± 63; lesion from C5 to L3) were included in this project. Muscle strength assessment of upper limbs was performed at admittance and discharge using MMT and myometry for the left and right side, and using Cybex dynamometer for the stronger side. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 23 publications
4
101
0
1
Order By: Relevance
“…We found a low correlation between the IMPT and MMT although the latter was performed by one orthopaedic surgeon. Similarly, in previous studies, only weak correlations between the MMT and IMPT were reported [12,18]. Numerous factors affect muscle strength including pain and ROM; however, muscle strength as determined by the MMT provides only limited and indistinct information regarding the tear size or FD of the rotator cuff muscle.…”
Section: Discussionmentioning
confidence: 58%
“…We found a low correlation between the IMPT and MMT although the latter was performed by one orthopaedic surgeon. Similarly, in previous studies, only weak correlations between the MMT and IMPT were reported [12,18]. Numerous factors affect muscle strength including pain and ROM; however, muscle strength as determined by the MMT provides only limited and indistinct information regarding the tear size or FD of the rotator cuff muscle.…”
Section: Discussionmentioning
confidence: 58%
“…77 Thirdly, it is limited in the ability to identify change for grades 4 and Literature review of physical capacity in spinal cord injury JA Haisma et al 5, and the registration of recovery is restricted by a ceiling effect. 49,52,[77][78][79] Fourthly, it seems less valid, because it has a limited correlation with isokinetic dynamometry, which is often regarded the gold standard for the assessment of muscle strength, but is not manageable in use. 44,77,80 The HHD score has shown to be valid, and has a good reliability in SCI, both with experienced and inexperienced examiners.…”
Section: Measuring Muscle Strength Of the Upper Extremitymentioning
confidence: 99%
“…49,52,[77][78][79] Fourthly, it seems less valid, because it has a limited correlation with isokinetic dynamometry, which is often regarded the gold standard for the assessment of muscle strength, but is not manageable in use. 44,77,80 The HHD score has shown to be valid, and has a good reliability in SCI, both with experienced and inexperienced examiners. 44,47,49 Muscle strength is an important component of physical capacity, and is related to functioning.…”
Section: Measuring Muscle Strength Of the Upper Extremitymentioning
confidence: 99%
“…At each session, a clinical testing of the muscles of the arm was performed, 16 and the patient was assigned to one of the three following groups according to the score of the TB and to the patient's progress in the surgical programme.…”
Section: Participantsmentioning
confidence: 99%
“…10,14 The tests aiming to evaluate the impairment of the hand are limited to the measurement of strength and joint motion. 11,[15][16][17] Most of the tests for the evaluation of the motor capacity of the hand 7,10,11,[18][19][20][21] are only performance tests and give no details on hand grip configurations during prehension. More global functional evaluations assess many functions in addition to hand performance 2,22,23 and are sensitive to additional variables (eg motivation, choice of the tasks or choice of the objects).…”
Section: Introductionmentioning
confidence: 99%